Digital intellectual property and privacy right in achieving the sustainable development goals using South Africa as a case study - Aroba Oluwasegun Julius; Ramchander Manduth (MATEC Web of Conferences)
A key barrier to achieving the Sustainable Development Goals (SDGs) is the intersection of intellectual property (IP) rights and privacy concerns, especially as reliance on digital technologies grows for economic and social progress. One of the critical ethical trade-offs in IP rights in IT in South Africa is the tension between protecting the interests of creators and promoting access to Information and knowledge, particularly in the context of the digital divide. This article, with a focus on South Africa, examines how digital IP and privacy rights impact SDG 9, 16 (Peace, Justice, and Strong Institutions). Loopholes, copyright protection is not always compatible with I.T. technology. Through legal analysis, policy evaluation, and case studies, it explores how IP protection can spur economic growth, ensure fair competition, and promote innovation while addressing privacy threats. The study also assesses existing policies' effectiveness in advancing SDG 9, 16, protecting privacy, and fostering innovation across vital industries. The study's conclusions advance knowledge of the intricate relationships between digital intellectual property, private property rights, and sustainable development. Particularly in the context of South Africa, the analysis provides insights into policy recommendations and best practices for practitioners, stakeholders, and policy makers to effectively exploit digital technologies while protecting individual rights and achieving the 9th and 16th SDGs.